Rare earth element cerium substituted Ca–Si–Mg system bioceramics: From mechanism to mechanical and degradation properties. Issue 14 (15th July 2021) - Su, Yun-Han; Pan, Cheng-Tang; Tseng, Yu-Sheng; Zhang, Ji; Chen, Wen-Fan
Abstract: Cerium (Ce)-substituted diopsides (CaMgSi2 O6 ) with enhanced mechanical strength and bioactivity were fabricated by precipitation method, followed by annealing at 1000 °C for 4 h. The mineralogical, morphological, in vitro biomineralization, degradation, and mechanical properties were investigated in order to assess the factors and mechanisms affecting the resultant properties. The X-ray diffractometer results showed that the onset of substitutional solid solubility in 0.25 mol Ce would result in new phase formation (cerium dioxide [CeO2 ], and magnesium silicate [MgSiO3 ]) further causing lattice instability. With increasing Ce dopant levels to 1.00 mol, the initial CaMgSi2 O6 phase was completely replaced by new phases. The field-emission scanning electron microscopy results indicated that the 0.25 mol Ce had the best biomineralization performance in vitro, while less hydroxyapatite precipitates were found with further increasing Ce dopant levels, suggesting the new phases led to the hindrance of precipitates. The weight loss values indicated that the high dissolution rate of ions in the matrix was observed in the pure sample, while the high readsorption rate of ions in the simulated body fluid (SBF) occurred with increasing Ce dopant levels. The pH value and the inductively coupled plasma-mass spectrometer results suggested that the release of Ca and Mg ions controlled the pH value. The mechanical strength of matrices before SBF immersion was related to the phase transformation, the elastic modulus of CeO2 and CaMgSi2 O6, and the release of Mg ions, while the mechanical strength of matrices after SBF immersion was dominated by the structure of matrices.